Respuesta :
Answer:
The answers are:
- x = 7
- y = 2
Step-by-step explanation:
5x + 3y = 41
2x + 3y = 20
- => 5x + 3y = 41
-2x - 3y = -20
- => 3x = 21
- => x = 7
- => 5(7) + 3y = 41
- => 35 + 3y = 41
- => 3y = 41 - 35
- => 3y = 6
- => y = 2
Conclusion:
Therefore, the answers are:
- x = 7
- y = 2
Hoped this helped
[tex]-BrainiacUser1357-[/tex]
Answer:
Step-by-step explanation:
It looks like you need to solve this system of equations.
That means we need to find a value for x and a value for y that makes both equations true.
Since both equations have a 3y in them, this system is ready to use a method called "elimination method"
Since the x terms are lined up, and the y terms are lined up, the equal signs are lined up, and the constants are lined up...you can subtract the bottom equation from the top equation.
5x + 3y = 41
2x + 3y = 20
Subtract and you will get
3x + 0y =21
We don't need to write that 0y, because it is 0.
3x = 21, now divide by 3
x = 7, almost finished!
Use x = 7 in either of the original equations to find y.
5x + 3y = 41 and x = 7
5•7+ 3y = 41
35 + 3y = 41
-35 -35
3y =6
y = 2
So the solution is x=7 and y=2
That can also be written as an ordered pair (7, 2)